2003
DOI: 10.1007/s00216-003-1762-z
|View full text |Cite
|
Sign up to set email alerts
|

Solid-phase extraction–spectrophotometric determination of uranium(VI) in natural waters

Abstract: A method for the extraction and determination of uranyl ion in natural waters using octadecyl bonded silica membrane disks modified with piroxicam and spectrophotometry with arsenazo(III) is proposed. The perconcentration step was studied with regard to experimental parameters such as amount of extractant, type and amount of eluent, pH, flow rates and tolerance limit of diverse ions on the recovery of uranyl ion. The limit of detection of the proposed method is 0.4 micro g L(-1) of uranyl. The method was appli… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
22
0

Year Published

2006
2006
2017
2017

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 56 publications
(23 citation statements)
references
References 31 publications
(32 reference statements)
1
22
0
Order By: Relevance
“…Also, the obtained LOD is comparable with that obtained by modified silica gel, 49 modified activated carbon 50 and ion imprinted polymer. 51 The linear range obtained by the proposed method is wider or better than those obtained by modified C18, 47 modified Amberlite XAD-4 52 and modified naphthalene. 53 In comparison with Amberlite XAD with the same LOD, SBA/EnSA has higher capacity.…”
Section: Comparison Of the Proposed Methods With Other Methodsmentioning
confidence: 85%
See 1 more Smart Citation
“…Also, the obtained LOD is comparable with that obtained by modified silica gel, 49 modified activated carbon 50 and ion imprinted polymer. 51 The linear range obtained by the proposed method is wider or better than those obtained by modified C18, 47 modified Amberlite XAD-4 52 and modified naphthalene. 53 In comparison with Amberlite XAD with the same LOD, SBA/EnSA has higher capacity.…”
Section: Comparison Of the Proposed Methods With Other Methodsmentioning
confidence: 85%
“…These ions can form complexes with the complexing reagent Arsenazo III; thus they have an interfering effect for the uranyl determination. A solution of EDTA (0.007 mol L -1 ) at the concentration of 10 and 50 times higher than of uranium 47,48 was successfully used as a masking agent for these interfering ions, respectively.…”
Section: Interference Studymentioning
confidence: 99%
“…Above this concentration, the study of uranyl(VI) hydrolysis is complicated due to the formation of polymeric species such as (UO 2 ) 2 (OH 2 ) 2 2+ , (UO 2 ) 3 (OH) 4 2+ and (UO 2 ) 3 (OH) 5 + . Several methods are utilised to extract uranium from wastewaters and process effluents, which include electromembrane extraction (Davarani et al, 2013), liquid-liquid extraction (Popov, 2012;Yang et al, 2002), solid phase extraction (Sadeghi et al, 2003) and ion exchange (Tavakoli et al, 2013). However, most of these techniques are both costly and ineffective, particularly when the concentration of uranium is very low (Blázquez et al, 2005).…”
Section: Introductionmentioning
confidence: 99%
“…1,2 The literature citation revealed that there are various analytical techniques for the estimation of uranium which include thin layer chromatography, 3 gravimetry, 4 titrimetry, 5 fluorimetry, 6,7 potentiometry, 8 polarography, 9 X-ray fluorescence, 10 inductively coupled plasma mass spectrometry. 11 In addition, spectrophotometric methods have also been employed to determine U(VI) in presence of thorium(IV), 12 ore leachates, 13 natural waters, [14][15][16] process streams of a uranium extraction plant 17 and soil. 18 Moreover, the gravimetric method generally requires the prior separation of interfering elements whereas multiple steps are involved in the titrimetric method.…”
Section: Introductionmentioning
confidence: 99%